Glass [videorecording (DVD)] : a portrait of Philip in twelve parts - Hicks, Scott; Glass, Philip (Koch Lorber Films ; Distributed by E1 Entertainment, 2009)
For 18 months, award-winning director Scott Hicks followed the legendary composer Philip Glass across three continents, creating a remarkable portrait of one of the greatest artists of all time. Allowed unprecedented access to Glass's working process and long time collaborators, Hicks provides a unique glimpse into the composer's life.